Common cortical and subcortical targets of the dorsolateral prefrontal and posterior parietal cortices in the rhesus monkey: evidence for a distributed neural network subserving spatially guided behavior - Selemon, LD (J Neurosci, 1988)
Common efferent projections of the dorsolateral prefrontal cortex and posterior parietal cortex were examined in 3 rhesus monkeys by placing injections of tritiated amino acids and HRP in frontal and parietal cortices, respectively, of the same hemisphere. Terminal labeling originating from both frontal and parietal injection sites was found to be in apposition in 15 ipsilateral cortical areas: the supplementary motor cortex, the dorsal premotor cortex, the ventral premotor cortex, the anterior arcuate cortex (including the frontal eye fields), the orbitofrontal cortex, the anterior and posterior cingulate cortices, the frontoparietal operculum, the insular cortex, the medial parietal cortex, the superior temporal cortex, the parahippocampal gyrus, the presubiculum, the caudomedial lobule, and the medial prestriate cortex. Convergent terminal labeling was observed in the contralateral hemisphere as well, most prominently in the principal sulcal cortex, the superior arcuate cortex, and the superior temporal cortex. In certain common target areas, as for example the cingulate cortices, frontal and parietal efferents terminate in an array of interdigitating columns, an arrangement much like that observed for callosal and associational projections to the principal sulcus (Goldman-Rakic and Schwartz, 1982). In other areas, frontal and parietal terminals exhibit a laminar complementarity: in the depths of the superior temporal sulcus, prefrontal terminals are densely distributed within laminae I, III, and V, whereas parietal terminals occupy mainly laminae IV and VI directly below the prefrontal bands. Subcortical structures also receive apposing or overlapping projections from both prefrontal and parietal cortices. The dorsolateral prefrontal and posterior parietal cortices project to adjacent, longitudinal domains of the neostriatum, as has been described previously (Selemon and Goldman-Rakic, 1985); these projections are also found in close apposition in the claustrum, the amygdala, the caudomedial lobule, and throughout the anterior medial, medial dorsal, lateral dorsal, and medial pulvinar nuclei of the thalamus. In the brain stem, both areas of association cortex project to the intermediate layers of the superior colliculus and to the midline reticular formation of the pons.(ABSTRACT TRUNCATED AT 400 WORDS)